Penentuan Tingkat Lahan Kritis Mangrove di Kecamatan Lembar, Kabupaten Lombok Barat Menggunakan Aplikasi GIS - Kusuma, I Made Bagus Nara; Buchori, Imam (Jurnal Pembangunan Wilayah dan Kota, 2021)
The coastal area of Lembar district has 80 hectares mangrove land on Lembar and Lembar Selatan village. But as time goes by, mangrove lands gradually eroded by land conversion. The purpose of this study is to measure the critical of mangrove land in Lembar District. The analysis uses GIS-based data with Landsat 8 OLI sattelite imagery and 3 determinants variables of the critical mangrove land, which are the type of land use, canopy density and soil resistance. Supervised classification method is used to analyze the landuse types, canopy density is generated from NDVI value, and the analysis of soil resistance obtained from soil type maps classification which then all of them is carried out to raster based weighted overlay process by Arc GIS. The result showed that mangrove land was in serious condition where 51% (41 hectares) of mangrove vegetation were in a state of severe damaged condition, 46% (39 hectares) were in a damaged condition and only 3% (2 hectares) were in good condition, so it was needed appropriate action from policy makers to deal with this problem in order to restore the sustainability of mangrove land in Lembar district.Â